Covid-19: Dampaknya terhadap Pendapatan Asli Daerah - Jouzar Farouq Ishak (Indonesian Accounting Research Journal, 2021)
This study assesses the comparison of local own-source revenue before and after the occurrence of Covid-19. This study uses a quantitative approach with a comparative research type. The types and sources of data used are secondary data. The research instrument used in this study is documentation related to the data on local own-source revenue in the realization of the 2019 and 2020 years. To analyse the data normality test, if the data is normally distributed, the test used is Parametric test Paired Sample t Test. The impact of the Covid-19 pandemic on the economy and finances is estimated not only to have an impact this year, but also to continue for the next few years. Therefore, it is necessary to carry out adequate anticipation followed by appropriate decision making, especially for government to be able to minimize negative impacts on the economic sector and finances.